Do servant leadership self-efficacy and benevolence values predict employee performance within the banking industry in the post-COVID-19 era: Using a serial mediation approach - Tasmeer Mujeeb; Noor Ullah Khan; Asfia Obaid; Guiling Yue; Hanieh Alipour Bazkiaei; Noor Azam Samsudin (Administrative Sciences, 2021)
Globally, the COVID-19 pandemic has brought significant implications to the workplace and highly impacted employee performance in every organization. In contemporary research, the scholars agree that leadership is one of the critical antecedents to predict employee performance in organizations. However, research is needed to investigate the mediating role of integral factors such as benevolence values (BV) and self-efficacy (SE) in predicting employee performance in the workplace. This study aimed to investigate the impact of key antecedents on employee performance in the banking industry. The findings reveal that the key antecedents, e.g., servant leadership (SL), self-efficacy (SE), and benevolence values (BV), have a direct positive relationship with employee performance (EP). Moreover, multiple indirect paths were tested, including serial mediation. This study used a quantitative methodology based on the positivist paradigm. A sample of 560 employees was randomly chosen. A survey questionnaire was distributed among them, and 400 were returned with a response rate of 70%, and the clean data of 400 employees was used for data analysis. The structural equation modeling (SEM) technique was employed using Smart PLS 3.3.3 software. The results confirmed that both SE and BV mediate the relationship between SL and EP. Likewise, BV mediates the relationship between SE and EP, and SE mediates the relationship between SL and BV. Finally, in serial mediation, the relationship between SL and EP is also established via SE and BV together as mediators.
Keywords: 350; benevolence values (BV); employee performance (EP); self-efficacy (SE); servant leadership (SL)